Sambandet mellan hästens huvud/halsposition och ryttarens rörelse i sadeln - Puhls, Sandra (2007)
Dressage schooling is not a subject that rests on science, it is a matter of dependable experience. So far there hasn't been so much research about it, but more and more is done. Especially the interaction between rider and horse is a nearly uninvestigated field. Riding skills is much about having the right position, and having the horses head and neck in different positions, but there are no research done that support or deny that this old "knowledge" is for the best for the horse.